Impact of Polymer Backbone Fluorination on the Charge Generation/Recombination Patterns and Vertical Phase Segregation in Bulk Heterojunction Organic Solar Cells - Shao, Yanqiu; Chang, Yuying; Zhang, Suju; Bi, Mingyue; Liu, Shengjian; Zhang, Daliang; Lu, Shirong; Kan, Zhipeng (Frontiers in Chemistry, 2020)
Incorporating fluorine (–F) substituents along the main-chains of polymer donors and acceptors is an effective strategy towards efficient bulk-heterojunction (BHJ) solar cells. Specifically, F-substituted polymers often exhibit planar conformations, leading to favorable packing and electronic coupling. However, the effects of fluorine substituents on the charge generation and recombination characteristics that determine the overall efficiency of BHJ active layers remain critically important issues to examine. In this report, two PBDT[2X]T polymer analogues –poly(4,8-bis((2-ethylhexyl)oxy)benzo[1,2-b:4,5-b′]dithiophene-thiophene) [PBDT[2H]T] and its F-substituted counterpart poly(4,8-bis((2-ethylhexyl)oxy)benzo[1,2-b:4,5-b′]dithiophene-3,4-difluoro-thiophene) [PBDT[2F]T] – are studied to systematically examine how –F substituents impact the blend morphology, charge generation, carrier recombination and extraction in BHJ solar cells. Considering the large efficiency differences between PBDT[2H]T- and PBDT[2F]T-based BHJ devices, significant emphasis is given to characterizing the out-of-plane morphology of the blend films as vertical phase-separation characteristics are known to have dramatic effects on charge transport and carrier extraction in polymer-fullerene BHJ solar cells. Herein, we use electron energy loss spectroscopy (EELS) in tandem with charge transport characterization to examine PBDT[2X]T-fullerene blend films. Our analyses show that PBDT[2H]T and PBDT[2F]T possess very different charge generation, recombination and extraction characteristics, resulting from distinct aggregation and phase-distribution within the BHJ blend films.